ANALISIS USHUL FIKIH TERHADAP DILALAT AL-MAFHUM AL-MUKHALAFAH (HASR, SIFAT, SYARAT, LAQAB, GAYAH, DAN ADAD) - Oktaviani, Ria; Fatmawati; Abidin, Zaenal (Khuluqiyya: Jurnal Kajian Hukum dan Studi Islam, 2025)
Interpretative challenges in Islamic law frequently arise from the absence of explicit rulings in primary texts. One method used to address this gap is Dilālat al-Mafhūm al-Mukhālafah, which derives legal meaning from the opposite implication of a given expression. This study aims to analyze six principal forms of mafḥūm al-mukhālafah: hasr (restriction), sifat (attribute), syarat (condition), laqab (designation), gāyah (limit), and ‘adad (number), and assess their legitimacy according to various Islamic legal schools. The research adopts a qualitative-descriptive approach through literature review of classical and modern ushul fiqh sources. Findings reveal that the acceptance of each form varies across schools of thought and depends on the context, linguistic structure, and strength of textual indication. Despite the differences, mafḥūm al-mukhālafah remains an essential tool in legal reasoning, especially in contemporary ijtihad where emerging issues require adaptable interpretations. This highlights the significance of mastering this concept to enrich Islamic legal discourse and strengthen contextual application of sharia rulings in modern society.